Identifying the Best Indicator of Assessing the Athletes Balance in the Sudden Perturbation Test - ebrahim abdi; Mansour Eslami; Mohammad r Taghi Pou (Biyumikānīk-i varzishī)
Objective: The aims of this study were to identify the most appropriate indicator to assess the balance in the sudden perturbation test conditions.